2011
DOI: 10.1186/1471-2199-12-40
|View full text |Cite
|
Sign up to set email alerts
|

Profile of small interfering RNAs from cotton plants infected with the polerovirus Cotton leafroll dwarf virus

Abstract: BackgroundIn response to infection, viral genomes are processed by Dicer-like (DCL) ribonuclease proteins into viral small RNAs (vsRNAs) of discrete sizes. vsRNAs are then used as guides for silencing the viral genome. The profile of vsRNAs produced during the infection process has been extensively studied for some groups of viruses. However, nothing is known about the vsRNAs produced during infections of members of the economically important family Luteoviridae, a group of phloem-restricted viruses. Here, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
59
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(67 citation statements)
references
References 56 publications
8
59
0
Order By: Relevance
“…The findings were also similar to the findings of Kreuze et al (2009) where they reported the prevalence of positive sense vsiRNAs over negative sense in virus-infected sweet potato plants. Another study conducted by Silva et al (2011) on cotton leafroll dwarf virus (CLDV) reported equal population of sense versus antisense derived vsiRNAs in virus-infected cotton plants. The ratio of sense versus antisense vsiRNAs was in the range of 1.1:1 to 1.25:1 in all the sRNA libraries generated from PVY-infected potato plants.…”
Section: Discussionmentioning
confidence: 98%
“…The findings were also similar to the findings of Kreuze et al (2009) where they reported the prevalence of positive sense vsiRNAs over negative sense in virus-infected sweet potato plants. Another study conducted by Silva et al (2011) on cotton leafroll dwarf virus (CLDV) reported equal population of sense versus antisense derived vsiRNAs in virus-infected cotton plants. The ratio of sense versus antisense vsiRNAs was in the range of 1.1:1 to 1.25:1 in all the sRNA libraries generated from PVY-infected potato plants.…”
Section: Discussionmentioning
confidence: 98%
“…Although 22 nt cucumber mosaic virus-vsRNAs produced by AtDCL2 were poor effectors of antiviral defense in Arabidopsis , predominant accumulation of 22-nt vsRNAs has been shown in previous studies on plant virus infections, such as cotton leafroll dwarf virus in cotton (Silva et al, 2011), cymbidium ring spot virus in N. benthamiana (Donaire et al, 2009), and turnip crinkle virus infections in Arabidopsis (Deleris et al, 2006). In these latter interactions, activity of the silencing-suppressor proteins P19 and P38, which, respectively, sequesters 21 nt duplex siRNAs (Vargason et al, 2003), and blocks AtDCL4 activity (Azevedo et al, 2010), could determine the observed high accumulation of 22 nt vsRNAs.…”
Section: The Vsrna Size Profile Is Different In the Two Hostsmentioning
confidence: 94%
“…The "basal" plant state found in Arabidopsis (or, for example, cotton (Silva et al, 2011)) is four Dicers, which presumably evolved through duplications of an ancestral Dicer (Margis et al, 2006) (Figure 48). Some plants (such as monocots) have higher counts of Dicer homologsthere are five in poplar and eight in rice; the additional Dicers evolved through duplications of one of the four "basic" plant Dicers (Margis et al, 2006;Kapoor et al, 2008;.…”
Section: Dicer Proteins -Dcl1-4 and Additional Dicer Family Membersmentioning
confidence: 99%